2009
DOI: 10.1111/j.1756-1051.2009.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectotypification of two Musa sections (Musaceae)

Abstract: The present work is part of a continuing study to revise the old names in Musa and aims to clarify the taxonomy in the sections Rhodoclamys and Callimusa. Lectotypes are designated here for Musa sect. Callimusa and M. sect. Rhodochlamys. These sections were first erected without the indication of a type species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Shepherd therefore suggested that the section should be divided into two groups, one of which would be ‘on the other side’ of M. acuminata , away from M. flaviflora, M. ornata and M. velutina (Häkkinen and Sharrock ). Further analyses of Musa diversity using various molecular techniques (Jarret and Gawel , Wong et al ) support the theory that the sections Rhodochlamys and Musa are closely related, as a clear distinction between the two sections could not be found in any of these studies (Bartos et al , Heslop‐Harrison and Schwarzacher , Häkkinen , , Li et al , Liu et al , Christelová et al , Hřibová et al , Xavier et al ). Rhodochlamys species, being very close to Musa species, provide a potential source of exploitable new genes, thus expanding the gene pool available to banana breeders.…”
Section: Musa Flaviflora N W Simmonds ( P 471) (Fig A–c B–g)mentioning
confidence: 86%
“…Shepherd therefore suggested that the section should be divided into two groups, one of which would be ‘on the other side’ of M. acuminata , away from M. flaviflora, M. ornata and M. velutina (Häkkinen and Sharrock ). Further analyses of Musa diversity using various molecular techniques (Jarret and Gawel , Wong et al ) support the theory that the sections Rhodochlamys and Musa are closely related, as a clear distinction between the two sections could not be found in any of these studies (Bartos et al , Heslop‐Harrison and Schwarzacher , Häkkinen , , Li et al , Liu et al , Christelová et al , Hřibová et al , Xavier et al ). Rhodochlamys species, being very close to Musa species, provide a potential source of exploitable new genes, thus expanding the gene pool available to banana breeders.…”
Section: Musa Flaviflora N W Simmonds ( P 471) (Fig A–c B–g)mentioning
confidence: 86%
“…The chromosome number for species in section Musa is 2n = 22 (Champion , Shepherd , Häkkinen and Sharrock , Häkkinen , , Li et al ).…”
Section: Musa Nagalandiana S Dey and Gogoi Sp Nov (Fig)mentioning
confidence: 99%
“…The chromosome number for species in section Musa is 2n = 22 (Champion 1967, Shepherd 1999, Häkkinen and Sharrock 2002, Häkkinen 2009, Li et al 2010).…”
Section: Musa Puspanjaliae R Gogoi and Häkkinen Sp Nov (Fig 1 2)mentioning
confidence: 99%